Strategi Adaptasi Pengusung Hoabinhian dalam Pemenuhan Kebutuhan Makanan - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2008)
AbstractThe presence of hoabinh site either in lowland or highland is characterized that there’s an adaptation effort of cultural to choose the dwelling location and complete the food. Artifact, ecofact, and fitur remains in sites at Bukit Kerang Pangkalan indicated that there’s a short & long period strategy.